Transferênce de metais pesados, flúor e radionuclídeos para solos agrícolas na bacia do rio Corumbataí (SP) - Da Conceição, Fabiano Tomazini; Bonotto, Daniel Marcos [UNESP] (My University, 2005)
The use of phosphate fertilizers and amendments in sugar cane crops may increase the concentration of some elements in soils, from where they would become available for plants (principally in acid soils) and transferred to me human food chain. This paper reports the transference of heavy metals (Cd, Cr, Cu, Ni, Pb and Zn), fluorine and radionuclides ( 238U, 234U, 226Ra, 232Th and 40K) from phosphate fertilizers and amendments to agricultural soils at Corumbatal River basin (SP). The products utilized and colleted in sugar cane crops at Corumbatai River basin are: phosphate fertilizers NPK 5:25:25 (two samples), limestones (three samples), phosphogypsum (two samples) and KCl (two samples). The heavy metals were determined by atomic absorption spectrometry (AAS), fluorine by potentiometry and radionuclides by alpha and gamma spectrometry. Heavy metals (17.8, 31.2, 75.2, 69.5, 138.8, 114.9 and 342.9 g/ha of Cd, Cr, Cu, Ni, Pb, Zn and F, respectively) and radionuclides (0.47, 0.16, 0.17 and 6.33 Bq/kg of soil to 238U, 226Ra, 232Th and 40K, respectively) incorporated in phosphate fertilizers and amendments are annually added in the sugar cane crops, but if utilized in accordance with the recommended rates, they do not raise the concentration levels in soils up to hazards values.

O uso de fertilizantes fosfatados e corretivos agrícolas nas plantações de cana-de-açúcar pode levar a um aumento na concentração de alguns elementos no solo, de onde passariam às plantas (principalmente em solos ácidos) e destas, como forragem ou alimento, ao animal e homem. Este trabalho visou estudar a transferência de metais pesados (Cd, Cr, Cu, Ni, Pb e Zn), flúor e radionuclídeos (238U, 234U, 226Ra, 232Th e 40K) de fertilizantes fosfatados e corretivos agrícolas para solos agrícolas na bacia do Rio Corumbataí (SP). Os produtos utilizados e coletados nas plantações de cana-de-açúcar na bacia do Rio Corumbataí são: fertilizantes fosfatados NPK 5:25:25 (duas amostras), calcários dolomíticos (uma amostra) e calcíticos (duas amostras), gesso (duas amostras) e KCl (duas amostras). Os metais pesados foram determinados por espectrometria de absorção atômica (AAS), o flúor por potenciometria, e os radionuclídeos por espectrometria alfa e gama. Metais pesados (17,8; 31,2; 75,2; 69,5; 138,8; 114,9 e 342,9 g/ha de Cd, Cr, Cu, Ni, Pb, Zn e F, respectivamente) e radionuclídeos (0,47; 0,16; 0,17 e 6,33 Bq/kg de solo para 238U, 226Ra, 232Th e 40K, respectivamente) existentes nos fertilizantes fosfatados e corretivos agrícolas são adicionados anualmente nas plantações de cana-de-açúcar, mas, se usados de acordo com as taxas recomendadas, não aumentam suas concentrações em solos para níveis perigosos.
Transference of heavy metals, fluorine and radionuclides to agricultural soils at Corumbataí River basin (SP)
Keywords: Agricultural soils; Phosphate fertilizers and amendments; Radionuclides and heavy metals; Sugar cane crops; agricultural soil; atomic absorption spectroscopy; cadmium; chromium; copper; fertilizer application; fluorine; gamma ray spectrometry; lead; nickel; phosphate; radionuclide; soil amendment; zinc; Brazil; Corumbatai Basin; Sao Paulo [Brazil]; South America; Phosphogypsum; Saccharum